„Uwertura dźwięku, który zabija”. O jednym wątku Wakacji nad Adriatykiem Zofii Posmysz - Tenczyńska, Anna (Res Facta Nova, 2025)
The aim of this paper is to examine the impact of extreme auditory perception experiences on the narrator of Zofia Posmysz’s novel Wakacje nad Adriatykiem [Vacations on the Adriatic], which might be read as a study of a forced hyperactivity of the subject of auditory perception, who reconstructs a story about her past based on unexpected sound stimuli heard again, but in completely different circumstances. Hence, the subject matter of the paper is the analysis of the relationship between listening, emotions, memory, and trauma of the novel’s narrator, who in her youth became an “ear witness” of a concentration camp reality. Her story is a testimony to the extent to which the compulsion to decipher all kinds of acoustic phenomena can affect human functioning in the world. Giving priority to the sense of hearing at the expense of the other senses is here associated with hyperacusis and other disorders of the post-traumatic stress. These experiences, which Posmysz described in her artistic language, are currently explored, for example, by Carolyn Birdsall in her studies on sound memories of the Nazi period, by Steve Goodman who analyzes them in the context of the relationship between sound and emotions, especially fear, or by James Martin Daughtry who examines them as a process of decoding sounds as tactical signs, serving, during a war, as a source of information that can save lives.